Pengaruh Ragam Metode Pembelajaran terhadap Capaian Prestasi Belajar - Iskandar, Azwar; Nasrul, Nasrul; Iskandar, Iskandar (Jurnal Imiah Pendidikan dan Pembelajaran, 2020)
This research aims to analyze the effect of variety of study methods on study performance.  Sample of this research was 56 students of finance diploma program got by purposive sampling method. Primary data was got by questionnaire. This research used research variable i.e. variety of study methods such as lecturing method, field trip method, STAD method and demonstration method as independent variables, and student’s study performance index as dependent variable. Using the multiple regression analysis, the research revealed that (i) lecturing method has significantly negative effect on student’s study performance index; (ii) field trip method has positive effect on student’s study performance index but has no significant; (iii) STAD method has positive effect on student’s study performance index but has no significant; (iv) demonstration method has positive effect on student’s study performance index but has no significant; and (v) all of study method simultaneous has no significant on student’s study performance index. In order to increase study performance, it is suggested to reduce the proportion of lecture method in the process of learning and increase the proportion of others study method such as field trip, STAD, and demonstration.